(untitled) (Bioscience Journal, 2014)
The extreme conditions in rocky outcrops allow the occurrence of desiccation tolerant species. One strategy of these plants to withstand water shortage is the accumulation of sugars. In this paper, we report sugar levels and profile of three ferns and one lycophyte naturally hydrated growing on rocky outcrops from Southeastern Brazil. Anemia species have higher sugar contents than Doryopteris collina and Selaginella sellowii. The analyzed species have different sugar profiles. The ferns have glucose, fructose and sucrose, and the lycophyte has glucose and trehalose.